Accelerometer-assessed physical activity and sedentary time among colon cancer survivors: associations with psychological health outcomes - Vallance, J.; Boyle, Terry; Courneya, K.; Lynch, B. (Springer New York LLC, 2015)
Purpose: The purpose of this study was to determine associations of objectively assessed moderate-to-vigorous intensity physical activity (MVPA) and sedentary time with psychological health outcomes including depression symptoms, anxiety symptoms, and overall satisfaction with life in colon cancer survivors. Methods: Colon cancer survivors (N = 180) from Alberta, Canada (n = 91), and Western Australia (n  = 89) completed a mailed survey that assessed depression symptom severity, state anxiety, and satisfaction with life (SWL). Sedentary time and MVPA were assessed using the Actigraph® GT3X+ accelerometer (60-s epochs) via a 7-day monitoring protocol. MVPA and sedentary time were corrected for wear time and then examined as quartiles (Q). Multivariate analysis of variance was used to examine associations of MVPA and sedentary time with psychological health. Results: There was a significant association between psychological health outcomes and objectively assessed MVPA [Wilks’ λ = 0.886, F(3382.2) = 2.156, p = 0.024] that suggested a small and significant association between MVPA and SWL (p = 0.032). A significant multivariate analysis of variance (MANOVA) [Wilks’ λ = 0.945, F(3159) = 3.1, p = 0.028] suggested participants meeting guidelines reported significantly fewer anxiety symptoms (M diff = −1.23, p = 0.027) and higher perceptions of SWL (M diff = 3.0, p = 0.008). No significant associations emerged for sedentary time [Wilks’ λ = 0.956, F(9382.3) = 0.788, p = 0.628].Conclusions: Contrary to previously published research using self-reports, objectively assessed MVPA and sedentary time were not associated with depression symptoms. Objectively assessed MVPA was associated with SWL and anxiety outcomes in colon cancer survivors. Implications for Cancer Survivors: Colon cancer survivors should continue to engage in regular and sustained MVPA for the accrual of psychological health benefits.